Dall’esuberanza tecnica al disincanto: il tecno-immaginario cyberpunk come tecnocritica? - Rumpala, Yannick (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The vision of technique is not monolithic and systematically enchanting in science fiction. It was even significantly shaken up in the 1980s by a particular current, cyberpunk, which offered a form of technical exuberance, but to say the least disturbing because it unfolded against a backdrop of social decay and economic neo-feudalism. Considering this sub-genre for what it allows to problematize, this contribution first shows how it suggests that the technological dynamic is inevitably an expansive dynamic and in what senses it contributes to redirect the speculative explorations of technical systems. It then sheds light on the questions that the works of cyberpunk explore in this way, in particular with regard to the effects on the human condition and the type of transformation that it undergoes. Finally, this contribution highlights the lines of flight that these fictions, through a play on the disenchantment of technical possibilities or the ways of diverting them, also bring out within the representations elaborated in the imaginary register.